Financial expenditure as a criterion for choosing the most appropriate method for ecological corridor implementation - RENAN A. OLIVEIRA; LILIANE M. NERY; VANESSA CÉZAR SIMONETTI; ARTHUR P. DOS SANTOS; ANTÔNIO CÉSAR G. MARTINS; DARLLAN C.C. SILVA (Anais da Academia Brasileira de Ciências)
Abstract To enhance landscape connectivity and mitigate the effects of forest fragmentation caused by urban expansion and human activities, ecological corridors (EC) have been proposed as a solution. This study evaluates the financial costs associated with land acquisition for the establishment of an EC between the Municipal Natural Park Biodiversity Corridors (PNMCBio) and the Ipanema National Forest (Flona Ipanema) using LSCorridors for EC modeling. Using land use and vegetation cover data as input, corridors were modeled based on four different resistance surfaces, which were generated in LSCorridors (pixel-based measure (PM), minimum (LMmin), average (LMavg), and maximum (LMmax) landscape measures. The models utilized a land use and vegetation cover resistance map from 2019. Additionally, an information plan was developed to assess the costs of land acquisition based on generic municipal maps. Among the LSCorridors methods, the PM approach resulted in 41.05% of the EC area being legally protected and yielded the lowest acquisition cost, totaling R$ (Brazilian real) 487,476.16. This proposed model can assist public managers in making informed decisions about EC proposals, thereby optimizing the allocation of public resources.